Plumboporphyria (ALAD deficiency) in a lead worker: a scenario for potential diagnostic confusion. Issue 12 (December 1993) - Dyer, J; Garrick, D P; Inglis, A; Pye, I F
Abstract : A lead worker developed bilateral wrist drop. At first this seemed to be a lead neuropathy but all his screening tests for blood and urine toxicity had been within the accepted safety limit during employment. Detailed investigation showed that he had plumboporphyria (ALAD deficiency) which had been symptom free until he was exposed to lead. Details of his porphyrin metabolism are presented.